Peran Angklung Sebagai Alat Diplomasi Budaya Untuk Menarik Wisatawan Amerika ke Indonesia - Alvianita, Silvia Hanif; Apriliani, Diah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Cultural diplomacy is one of the increasingly important forms of soft power in international relations. Indonesia utilizes traditional arts, one of which is angklung, as an instrument of cultural diplomacy to strengthen the country’s positive image in the eyes of the world. This study discusses how angklung is used as a tool of cultural diplomacy in the United States, the promotional strategies undertaken, as well as its impact on the increase in American tourists to Indonesia. The research method used was qualitative descriptive with data collection techniques in the form of interviews, documentation, and literature study. The study results show that angklung performances successfully improve cross-cultural understanding, build a positive image of Indonesia, and become a cultural tourism attraction. However, there are challenges in the form of limitations of the American public’s promotion and understanding of angklung. This study affirms the importance of sustainable strategies for strengthening cultural diplomacy through traditional performing arts..